2018
DOI: 10.1007/s11307-017-1153-z
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Responses to Amyloid-Beta Progression in a Mouse Model of Alzheimer’s Disease

Abstract: Purpose: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by amyloidbeta (Aβ) deposition, hyperphosphorylation of tau, and neuroinflammation. Astrocytes, the most abundant glial cell type in the nervous system, respond to neurodegenerative disorders through astrogliosis, i.e., converting to a reactive inflammatory state. The aim of this study was to investigate how in vivo quantification of astrogliosis using positron emission tomography (PET) radioligand deuterium-L-[ 11 C]deprenyl ([ 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 48 publications
7
29
0
2
Order By: Relevance
“…However, importantly, clustering of GFAP was observed both in the EC and HPC of 10-month-old APP/PS1 mice, and coverage of this clustered GFAP in the HPC was increased as expected. Considering that clustered GFAP was more prominent in APP/PS1 mice, and we observed a similar pattern of Aβ plaque load in parallel series of the same brain stained for Aβ, clustering of GFAP is probably due to accumulation of GFAP around Aβ plaques [76]. The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP+ astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [77].…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 74%
“…However, importantly, clustering of GFAP was observed both in the EC and HPC of 10-month-old APP/PS1 mice, and coverage of this clustered GFAP in the HPC was increased as expected. Considering that clustered GFAP was more prominent in APP/PS1 mice, and we observed a similar pattern of Aβ plaque load in parallel series of the same brain stained for Aβ, clustering of GFAP is probably due to accumulation of GFAP around Aβ plaques [76]. The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP+ astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [77].…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 74%
“…However, importantly, clustering of GFAP was observed both in the EC and HPC of 10-month-old APP/PS1 mice, and coverage of this clustered GFAP in the HPC was increased as expected. Considering that clustered GFAP was more prominent in APP/PS1 mice, and we observed a similar pattern of Aβ plaque load in parallel series of the same brain stained for Aβ, clustering of GFAP is probably due to accumulation of GFAP around Aβ plaques [75]. The reduction in global versus the increase in clustered GFAP coverage is in line with a previous study where general astroglial cytoskeletal atrophy was observed, while GFAP + astrocytes surrounding Aβ plaques were hypertrophic in the HPC of 18-month-old 3xTG AD mice [76].…”
Section: Modulation Of Astrocytes By Aβ Overexpression In Hpc and Ecsupporting
confidence: 74%
“…The pathogenesis is characterized by amyloid‐β deposition, hyperphosphorylation of tau, and neuroinflammation along with dramatic astrogliosis (Hascup et al, ). The astrogliosis occurs following the overexpression of enzyme monoamine oxidase‐B during amyloid‐β plaque evoked reactive inflammation (Olsen et al, ). Astrocytic response by astrogliosis, injury and atrophy can be either neuroprotective or deleterious.…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%